Optimization of a Weak 3′ Splice Site Counteracts the Function of a Bovine Papillomavirus Type 1 Exonic Splicing Suppressor In Vitro and In Vivo - Zheng, Zhi-Ming (American Society for Microbiology, 2000)
Alternative splicing is a critical component of the early to late switch in papillomavirus gene expression. In bovine papillomavirus type 1 (BPV-1), a switch in 3′ splice site utilization from an early 3′ splice site at nucleotide (nt) 3225 to a late-specific 3′ splice site at nt 3605 is essential for expression of the major capsid (L1) mRNA. Three viral splicing elements have recently been identified between the two alternative 3′ splice sites and have been shown to play an important role in this regulation. A bipartite element lies approximately 30 nt downstream of the nt 3225 3′ splice site and consists of an exonic splicing enhancer (ESE), SE1, followed immediately by a pyrimidine-rich exonic splicing suppressor (ESS). A second ESE (SE2) is located approximately 125 nt downstream of the ESS. We have previously demonstrated that the ESS inhibits use of the suboptimal nt 3225 3′ splice site in vitro through binding of cellular splicing factors. However, these in vitro studies did not address the role of the ESS in the regulation of alternative splicing. In the present study, we have analyzed the role of the ESS in the alternative splicing of a BPV-1 late pre-mRNA in vivo. Mutation or deletion of just the ESS did not significantly change the normal splicing pattern where the nt 3225 3′ splice site is already used predominantly. However, a pre-mRNA containing mutations in SE2 is spliced predominantly using the nt 3605 3′ splice site. In this context, mutation of the ESS restored preferential use of the nt 3225 3′ splice site, indicating that the ESS also functions as a splicing suppressor in vivo. Moreover, optimization of the suboptimal nt 3225 3′ splice site counteracted the in vivo function of the ESS and led to preferential selection of the nt 3225 3′ splice site even in pre-mRNAs with SE2 mutations. In vitro splicing assays also showed that the ESS is unable to suppress splicing of a pre-mRNA with an optimized nt 3225 3′ splice site. These data confirm that the function of the ESS requires a suboptimal upstream 3′ splice site. A surprising finding of our study is the observation that SE1 can stimulate both the first and the second steps of splicing.